2018
DOI: 10.2174/1573399814666180125100917
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Diabetic Complications in Newly Diagnosed versus Known Type 2 Diabetic Subjects in a Sample of Alexandria Population, Egypt

Abstract: The present study confirms that a considerable proportion of people with T2DM have microvascular complications and/or PAD at the time of, and possibly years before diagnosis. Having shown that, it is strongly recommended to apply appropriate screening strategies for subjects with diabetes at the time of diagnosis. Finally, these results should be considered as a call for action for the health care planners and providers in our region to plan for early screening for diabetes and its complications to reduce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 43 publications
3
56
1
Order By: Relevance
“…It should be noted that undiagnosed T2DM is a major problem, and the exact duration of T2DM is often unknown [50]. In a considerable number of patients, vascular complications are detected at the same time as the diagnosis of T2DM [51,52]. The finding that the odds of vascular and microvascular complications were higher in patients on lifestyle modification + OAD + insulin as part of their T2DM therapeutic regimen is consistent with previous research [53].…”
Section: Discussionsupporting
confidence: 85%
“…It should be noted that undiagnosed T2DM is a major problem, and the exact duration of T2DM is often unknown [50]. In a considerable number of patients, vascular complications are detected at the same time as the diagnosis of T2DM [51,52]. The finding that the odds of vascular and microvascular complications were higher in patients on lifestyle modification + OAD + insulin as part of their T2DM therapeutic regimen is consistent with previous research [53].…”
Section: Discussionsupporting
confidence: 85%
“…3 Patients with newly diagnosed diabetes in Alexandria, Egypt, already had evidence of diabetes complications, for example, neuropathy (3%), and nephropathy, retinopathy and peripheral artery disease (10% for each); the prevalence of these complications was 29%-48% for patients with known diabetes. 101 Complications (nephropathy and peripheral neuropathy) were also prevalent in the UAE for people with type 2 diabetes (44% and 37%, respectively) and prediabetes (29% and 13%, respectively); 73% of type 2 diabetes patients had retinopathy here (not investigated in prediabetes). 7 Importantly, complications of diabetes are already evident is some people with prediabetes.…”
Section: Discussionmentioning
confidence: 90%
“…Totally, 1,278 studies were retrieved, of which, 1,261 studies were found from six international databases and the remaining 17 were through manual search. Databases includes; PubMed 161 [44,45], 2 research paper from Egypt [46,47],the remaining was from Ghana [15],Uganda [48],and Tanzania [49]. The highest prevalence of diabetic peripheral neuropathy (83.4%) and the lowest (7.5%) were reported from Nigeria.…”
Section: Search Resultsmentioning
confidence: 99%